Developments and challenges in retrofitting fire-affected concrete structures: A review - Malik, Manisha; Bhattacharyya, Sriman K. (Journal of Structural Engineering, 2024)
Structural Fire Engineering (SFE) is important for ensuring the safety of structures / buildings and their occupants during a fire. Recent advancements in SFE have led to the development of fire-resistant materials and systems, as well as retrofitting strategies that aim to address challenges posed by different building types and fire scenarios. However, fire prevention and protection measures alone are insufficient. Despite protection measures, many a times structures / structural elements do get affected. Hence, post-fire assessments of the state of a structure / structural elements are essential to determine the appropriate course of actions. To improve fire safety, it is crucial to understand the role of human behaviour, education, signage, and technology. The present paper outlines various ways to reduce the risk of fire hazards, including active and passive fire protection measures and the use of smart sensors and fireresistant materials. Additionally, the paper covers the use of passive fire protection systems and various strengthening techniques to retrofit concrete structural members, highlighting the associated developments. The paper also discusses different methods for assessing fire damage, such as colourimetry, strain energy dissipation, temperature field history calculation, and studying changes in the concrete microstructure using X-ray diffraction. Finally, the paper explores factors affecting the selection of a suitable retrofitting technique and approaches proposed by different authors to choose the appropriate retrofit methodology based on damage assessment.